Asymptotic behavior of solutions of Monge–Ampère equations with general perturbations of boundary values - Jia, Xiaobiao; Li, Xuemei (Comptes Rendus. Mathématique)
In this paper, we consider the asymptotic behavior of solutions of Monge–Ampère equations with general boundary value conditions in half spaces, which reveals the accurate effect of boundary value condition on asymptotic behavior and improves the result in [13].